Creative thinking skills students in physics on solid material elasticity - Batlolona, John Rafafy; Dıantoro, Markus; Wartono; latıfah, Eny (Journal of Turkish Science Education, 2024)
The research mixed method aims to investigate students' creative thinking skills about elasticity in physics. The students' creative thinking skills were measured by diagnostic tests developed by researchers and validated by theoretical physics. The instrument included several indicators of critical thinking skills including fluency, flexibility, originality, and elaboration. This study involved 58 students of 11th grade of public senior high school 8, Malang. The research findings showed that students who were learning with the PBL and conventional approach had good scores in originality and fluency. Particularly in the PBL classes, the highest scores of critical thinking skills were achieved on parallel and parallel spring topics, while in conventional classrooms, the highest scores of critical thinking skills were achieved on the stress, tension, and topic of Young's modulus. Both the PBL and conventional classes got the lowest score on Hooke's law topic. The t-test results showed that there was no difference between the pretest score of PBL students and the conventional student's pretest score. However, the difference was found in post-test scores. In conclusion, the PBL was recommended to develop or enhance students' creative thinking. Future research was expected to fully examine the effect of the PBL on student motivation, and high-level thinking with or without moderator variables. In addition, it was also necessary to conduct other researches that aims to analyze the relationship between pretest and post-test students in creative thinking after engaging in the PBL classes.
Keywords: Creative thinking skills; solid material elasticity; PBL